Advances in artificial life 9th European conference, ECAL 2007, Lisbon, Portugal, September 10-14, 2007, proceedings - Costa, Fernando Almeida e. (Springer eBooks., 2007)
The two-volume set LNAI 5777 and LNAI 5778 constitutes the thoroughly refereed post-conference proceedings of the 10th European Conference, ECAl 2009, held in Budapest, Hungary, in September 2009. The 141 revised full papers presented were carefully reviewed and selected from161 submissions. The papers are organized in topical sections on evolutionary developmental biology and hardware, evolutionary robotics, protocells and prebiotic chemistry, systems biology, artificial chemistry and neuroscience, group selection, ecosystems and evolution, algorithms and evolutionary computation, philosophy and arts, optimization, action, and agent connectivity, and swarm intelligence.